From smart city to intelligence in urban operations: the case of Centro de Operações Rio (Revista LIDER, 2020)
The city of Rio de Janeiro has geographic-environmental peculiarities which areworld-renowned, and which are also part of an urban problem that demands more and more attention from the government. Urban challenges are pressing for an innovative attitude of government, as well as of its citizens. Centro de Operações Rio (COR) was created to support the management of the urban infrastructure and logistics operations in the city, by applying modern technologies and the integration of more than 30 public agencies and other utilities services providers, all in the same area. This research aims to characterize the changes occurred in the city of Rio de Janeiro after the introduction of the technological artefact COR, identifying an adherence with spatial transformations and the concept of smart city.We also try to characterize the operational logistics, discussing some of the theoretical precepts of the concept of smart city, in enforcement mechanisms in the implementation and operationalization of COR, and articulating as possible convergences between these preconceptions and that which we observed in the city of Rio de Janeiro. Finally, the research is a case study, based on Systematic Literature Review (SLR), semi-structured interviews and participant-observation.